INVESTIGATING STUDENTS’ FAMILIARITY WITH CONVERSION, AN ENGLISH WORD FORMATION PROCESS - Krismalita Sekar Diasti; Barli Bram (IAIN Syekh Nurjati Cirebon, 2020)
One of the paramount aspects of acquiring a language is mastering the vocabulary. One way to enrich our vocabulary is by familiarizing ourselves with word formation process. This study aimed to investigate students’ familiarity with a word formation process called conversion. This was a descriptive quantitative study. Using Google Forms, the researchers distributed a questionnaire containing statements on conversion to collect data. The participants were 10 first year students of the English Language Education Study Program (ELESP) of Sanata Dharma University, Yogyakarta. The researchers calculated the students’ correct and incorrect answers. Results showed that most of the students were unfamiliar with conversion, one of the word formation processes, especially the conversion involving verbs to nouns (50%) and adjectives to nouns (50%). Most students were knowledgeable about the conversion from nouns to verbs (80%). One of the implications is that ELESP students study conversion, one of the word formation processes in English, to enrich their vocabulary items.